Gestational Trophoblastic Disease Presents as an Ectopic Tubal Pregnancy, a Rare Entity. (6th August 2019) - Al-Maghrabi, Haneen; Saleh, Daniyah; Meliti, Abdelrazak
Abstract : Ectopic molar pregnancy is an uncommon event in clinical practice. In this paper, we report a case of ectopic complete molar pregnancy in a 39-year-old lady who presented to the emergency department with lower abdominal pain, abdominal distention, and low-grade fever. Based on radiological and laboratory investigations, the differential diagnosis included ruptured ectopic pregnancy versus metastatic diseases. Ectopic hydatidiform molar pregnancies can occur at any extrauterine pelvic sites, yet more frequently affecting fallopian tubes. The histopathological examination remains the gold standard for the diagnosis.